2016
DOI: 10.1515/jcim-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic properties of spices of the traditional Cameroonian dish “Nkui” in ovariectomized Wistar rats

Abstract: These results suggest that the spices of "Nkui" contain estrogenic phytoconstituents and this traditional food may be considered as functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Its presence in nkui could possibly be linked to the therapeutic and estrogenic use of the soup for lactating mothers in Cameroon, as demonstrated in an in vivo study by Tchoupang et al. (2016). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its presence in nkui could possibly be linked to the therapeutic and estrogenic use of the soup for lactating mothers in Cameroon, as demonstrated in an in vivo study by Tchoupang et al. (2016). …”
Section: Resultsmentioning
confidence: 99%
“…Linalool (Figure 1) is a terpene alcohol which occurs in plants, spices, tree barks and possess anti-inflammatory and chemoprotective activity (Peana et al, 2002;Ravizza, Gariboldi, Molteni, & Monti, 2008). Its presence in nkui could possibly be linked to the therapeutic and estrogenic use of the soup for lactating mothers in Cameroon, as demonstrated in an in vivo study by Tchoupang et al (2016).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the western region of Cameroon, the traditional mixture named "Nkui", which is composed of several spices [1], is usually consumed by women for several weeks before and after childbirth [2]. In in vivo studies, "Nkui" has exhibited estrogenic properties and results showed a reduction of cardiovascular risk in ovariectomized rats.…”
Section: Introductionmentioning
confidence: 99%
“…In in vivo studies, "Nkui" has exhibited estrogenic properties and results showed a reduction of cardiovascular risk in ovariectomized rats. One component of this mixture consists of the fruits of Solanum gilo Raddi (Solanaceae) [1]. The taxonomic classification of this species has been quite controversial.…”
Section: Introductionmentioning
confidence: 99%